The correlation between the subjective perception of health and the characteristics of cardiovascular function in swimmers and non-swimmers - Dobrin A.V.; Elnikova O.E.; Rogova N.S. (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study was to discern the characteristics of the connection between the state of health and the control of heart rate in older preschoolers who participate in swimming classes and those who do not engage in sports activities. Methods and structure of the study. The study involved 44 participants aged between 5 and 7 years old, with an average age of 6,29 ± 0,7 years. To assess the internal picture of health, we employed the Rapid Diagnosis of the Child questionnaire and the Attitude to Health questionnaire. To analyze the cardiac rhythm variability, we utilized the OMEGA-M software and hardware complex. Results and conclusions. The characteristics of the internal health status vary between children who participate in swimming activities and those who do not. Children who participate in swimming activities exhibit a lower level of internal health compared to their peers who do not participate. The level of internal health is linked to the specific features of heart rate variability. Preschoolers who participate in swimming activities demonstrated an increase in the activity of the sympathetic division of the autonomic nervous system during cardioregulation, suggesting a moderate stress on the body’s regulatory systems.